Incidence of acute myocardial infarction-related cardiogenic shock during corona virus disease 19 (COVID-19) pandemic. (December 2020) - Lauridsen, M.D.; Butt, J.H.; Østergaard, L.; Møller, J.E.; Hassager, C.; Gerds, T.; Kragholm, K.; Phelps, M.; Schou, M.; Torp-Pedersen, C.; Gislason, G.; Køber, L.; et al.
Abstract: Aims: The hospitalization of patients with MI has decreased during global lockdown due to the COVID-19 pandemic. Whether this decrease is associated with more severe MI, e.g. MI-CS, is unknown. We aimed to examine the association of Corona virus disease (COVID-19) pandemic and incidence of acute myocardial infarction with cardiogenic shock (MI-CS). Methods: On March 11, 2020, the Danish government announced national lock-down. Using Danish nationwide registries, we identified patients hospitalized with MI-CS. Incidence rates (IR) and incidence rate ratios (IRR) were used to compare MI-CS before and after March 11 in 2015–2019 and in 2020. Results: We identified 11, 769 patients with MI of whom 696 (5.9%) had cardiogenic shock in 2015–2019. In 2020, 2132 MI patients were identified of whom 119 had cardiogenic shock (5.6%). The IR per 100, 000 person years before March 11 in 2015–2019 was 9.2 (95% CI: 8.3–10.2) and after 8.9 (95% CI: 8.0–9.9). In 2020, the IR was 7.5 (95% CI: 5.8–9.7) before March 11 and 7.7 (95% CI: 6.0–9.9) after. The IRRs comparing the 2020-period with the 2015–2019 period before and after March 11 (lockdown) were 0.81 (95% CI: 0.59–1.12) and 0.87 (95% CI: 0.57–1.32), respectively. The IRR comparing the 2020-period during and before lockdown was 1.02 (95% CI: 0.74–1.41). No difference in 7-day mortality or in-hospital management was observed between study periods. Conclusion: We could not identify a significant association of the national lockdown on the incidence of MI-CS, along with similar in-hospital management and mortality in patients with MI-CS.